Functional characterization of CHEK2 variants in a Saccharomyces cerevisiae system - Delimitsou, Angeliki; Fostira, Florentia; Kalfakakou, Despoina; Apostolou, Paraskevi; Konstantopoulou, Irene; Kroupis, Christos; Papavassiliou, Athanasios G; Kleibl, Zdenek; Stratikos, Efstratios; Voutsinas, Gerassimos E; Yannoukakos, Drakoulis (Human mutation, 2019)
Genetic testing for cancer predisposition leads to the identification of a number of variants with uncertain significance. To some extent, variants of BRCA1/2 have been classified, in contrast to variants of other genes. CHEK2 is a typical example, in which a large number of variants of unknown clinical significance were identified and still remained unclassified. Herein, the CHEK2 variant assessment was performed through an in vivo, yeast-based, functional assay. In total, 120 germline CHEK2 missense variants, distributed along the protein sequence, and two large in-frame deletions were tested, originating from genetic test results in breast cancer families, or selected from the ClinVar database. Of these, 32 missense and two in-frame deletions behaved as non-functional, 73 as functional, and 15 as semi-functional, after comparing growth rates of each strain with positive and negative controls. The majority of non-functional variants were localized in the CHK2 kinase and forkhead-associated domains. In vivo results from the non-functional variants were in agreement with in silico predictions, and, where available, with strong breast cancer family history, to a great extent. The results of the largest, to date, yeast-based assay, evaluating CHEK2 variants, can complement and assist in the classification of rare CHEK2 variants with unclear clinical significance.
Keywords: alely; Saccharomyces cerevisiae; Protein Conformation; Alleles; výpočetní biologie; genetická predispozice k nemoci; Checkpoint Kinase 2; Models, Molecular; Amino Acid Substitution; Gene Frequency; checkpoint kinasa 2; lidé; Genetic Predisposition to Disease; Pedigree; Genetic Association Studies; rodokmen; Mutation; substituce aminokyselin; mutace; genetické asociační studie; frekvence genu; molekulární modely; Computational Biology; Humans; konformace proteinů